Exogenous surfactant, a role in the adult acute respiratory distress syndrome? - Busani, S.; Girardis, M.; Pasetto, et al., A. (Acta Biomedica Atenei Parmensis, 2012)
Adult ARDS still represents a high mortality disease. Exogenous surfactant trials in adults with ARDS failed to prove benefit on survival; anyway limitations of these studies were strongly debated. An Italian group of intensive care doctors, proceeding from trials observations, shared an exogenous surfactant protocol for the treatment of ARDS in adult patients.